Implementation of the Children Learning in Sciences (CLiS) Learning Model to Improve Students' Science Learning Outcomes - Hilda Hilda; Yusdin Mahmudin Gagaramusu; Pahriadi Pahriadi; Zulnuraini Zulnuraini; Nuraini Nuraini (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to explain the application of the Children Learning in Science (CLiS) model in improving the science learning outcomes of fourth-grade students at SD Inpres 1 Tondo. This study uses the Classroom Action Research (CAR) method, which focuses on improving the quality of learning in the classroom. This model follows four stages of the Kemmis and McTaggart cycle: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. This study was conducted during the 2024/2025 academic year, involving 28 fourth-grade students as research subjects. Data were collected using test and non-test techniques. Non-test methods include interviews, classroom observations, and documentation, while the test method uses multiple-choice questions to assess students' understanding of science material. In Cycle I, the percentage of students achieving The classical approach was used to In Cycle I, student achievement using the classical approach increased to 64.29%, compared to 50% in the pre-action phase, showing an increase of 14.29%. In Cycle II, the percentage reached 100%. This shows an increase of 35.71% compared to Cycle I. These results indicate that the CLiS learning model has a significant influence on improving students' science learning outcomes. Therefore, the application of the CLiS model can be said to be an effective strategy to improve the learning achievement of fourth-grade students of SD Inpres 1 Tondo